An Equilibrium Model of Imperfect Hedging: Transaction Costs, Heterogeneity in Risk Aversion, and Return Volatility - Loewenstein, Mark; Qin, Zhenjiang (Review of Financial Studies, 2025)
Abstract Financial transaction taxes, or generally transaction costs, are salient in derivatives markets and seldom studied in equilibrium models. We study a tractable model with proportional transaction costs where agents trade a derivative with nonlinear payoffs to hedge nontraded endowments. We show that trade is sustained in an equilibrium with transaction costs only if there is sufficient heterogeneity in risk aversion. When there is trade, the equilibrium return variance increases in transaction costs. These results are driven by how mean-variance demands, hedging demands, and asymmetry of no-transaction region widths determine the equilibrium Sharpe ratio and return volatility when transaction costs change.